2012
DOI: 10.1039/c2jm16105b
|View full text |Cite
|
Sign up to set email alerts
|

Study on formaldehyde gas-sensing of In2O3-sensitized ZnO nanoflowers under visible light irradiation at room temperature

Abstract: In 2 O 3 -sensitized flowerlike ZnO with visible light photoelectric response properties were synthesized by a facile two-step process, and characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), EDAX, HRTEM and UV-vis diffuse reflectance spectroscopy. The results revealed that In 2 O 3 nanoparticles have grown and eventually coalesced on the surface of the flowerlike ZnO successfully, and the samples exhibited significant response to visible light. The photoelectric gas-sensing of the In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 49 publications
1
54
0
Order By: Relevance
“…Initially, ZnO×3/support clearly exhibits an absorption edge at around 403 nm, while α-alumina support does not show any absorption between 300~800 nm. This result indicates that the successful deposition of ZnO particles on the support (Han et al, 2012). In view of no absorption between 300~800 nm on pure ZIF-8 materials (Esken et al, 2011), the absorption edge blue shift to 392 nm on ZIF-8 seed/support can be considered as the increase of the band gap in correlation to the intimate interfacial interaction between…”
Section: Gas Permeationmentioning
confidence: 90%
“…Initially, ZnO×3/support clearly exhibits an absorption edge at around 403 nm, while α-alumina support does not show any absorption between 300~800 nm. This result indicates that the successful deposition of ZnO particles on the support (Han et al, 2012). In view of no absorption between 300~800 nm on pure ZIF-8 materials (Esken et al, 2011), the absorption edge blue shift to 392 nm on ZIF-8 seed/support can be considered as the increase of the band gap in correlation to the intimate interfacial interaction between…”
Section: Gas Permeationmentioning
confidence: 90%
“…Fig S4 illustrates that the response and recover procedures of the HCHO sensing. The response and recovery times are 5 s and 1.3 s respectively, which were really short compared to that reported before [4,5,7,13,[30][31][32][33][34]. The HCHO detection limit, response time and recovery time of Sample 1 and those value reported before are listed in table S1, which have suggested that the Sample 1 was sensitivity to HCHO molecules and the adsorption and desorption of the HCHO molecules on the surfaces of Sample 1 were both rapid.…”
Section: Resultsmentioning
confidence: 73%
“…The curve describes changes in the electrical signal from Sample 1, which were caused by the reactions between the surfaces of Sample 1 and the HCHO molecules [2][3][4][5][6][7][19][20][21]. The changes indicate that the HCHO detection limit of Sample 1 is 80 ppb, lower than those (≥0.5 ppm) of the reported semiconductor-based sensors [4,5,7,13] and the health standard limitation (100 ppb) [1], and so meets the requirement of practical applications. Moreover, the HCHO sensing of Sample 1 is repeatable, as both the first peak and the third peak are all contain 100 ppb HCHO and the response of these two peaks are same, show in Fig.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Among the large family of ZnO nanostructures, NFs have several advantages such as high surface area‐to‐volume ratio and a short conduction path for electrons to transport. Therefore different researchers have used NF‐like structures for the fabrication of different devices such as solar cells, sensors, bio‐devices and display applications 22–26. Nevertheless, there is no report published on harvesting piezoelectric potential from ZnO NF‐like nanostructures.…”
Section: Introductionmentioning
confidence: 99%